2015
DOI: 10.5901/mjss.2016.v7n1p159
|View full text |Cite
|
Sign up to set email alerts
|

Hypocritical Behavior and Organization Size: A Game-theory Approach

Abstract: This article seeks to address hypocritical behavior in interpersonal communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…This finding is in alignment with prior studies as researchers drew our attention to the importance of corporate morality for employees' psychology and behavioral intentions (Babu et al. , 2019; Hadadian et al. , 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is in alignment with prior studies as researchers drew our attention to the importance of corporate morality for employees' psychology and behavioral intentions (Babu et al. , 2019; Hadadian et al. , 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Goswami et al (2018) investigated employees' PCH measuring its impacts on employees' intentions to quit and attitude towards corporations. Yet other studies found employees' PCH to reduce their interest in existing jobs, increase anxiety and have intentions to disassociate from such employers (Hadadian et al, 2015;Miao and Zhou, 2020). Thus, while PCH tarnishes corporations' legitimacy and credibility among employees, a dominant amount of literature reports of PCH affecting employees' psychology and behavioral intentions, specifically employees' attitudes towards corporation and turnover intentions (Babu et al, 2019;Goswami and Ha-Brookshire, 2016).…”
Section: Impacts Of Employees' Pchmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of literature suggests that corporate hypocrisy can be created in consumers', employees', and investors' minds (Goswami & Ha-Brookshire, 2016;Janney & Gove, 2011;Wagner et al, 2009). Such perceptions of corporate hypocrisy can be problematic for the corporations' reputations and even economic performance (Brunsson, 1993b;Cour & Kromann, 2011;Hadadian, Navidi, Digehsara, & Sabet, 2016;Wagner et al, 2009). Given the background discussed above, perceived corporate hypocrisy is an important topic within the retail sector.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Such perceptions not only jeopardize stakeholders' overall trust, loyalty, and general attitude towards those corporations but can also generate discomfort, psychological distance and alienation, turnover intentions, a lack of commitment, and job dissatisfaction, particularly among employees (Abraham, 2000;Arli, Grace, Palmer, & Pham, 2017;Greenbaum, Mawritz, & Piccolo, 2015;Kim, Hur, & Yeo, 2015;Philippe & Koehler, 2004;Shim & Yang, 2016;Simons, 2002). Additionally, such perceptions can be problematic for the corporations' reputations and even economic performances (Brunsson, 1993;Cour & Kromann, 2011;Hadadian, Navidi, Digehsara, & Sabet, 2016;Wagner et al, 2009). Given that employees' attitudes, behaviors, and perceptions have important consequences on businesses' overall performances (Chambers et al, 1998;Lawler, 1992;Mathieu & Zajac, 1990;Meyer et al, 1997;Pfeffer, 1994), PCH among employees needs to be further investigated.…”
Section: Summary Of the Studymentioning
confidence: 99%